Integrated mineralogical analysis (QEMSCAN and DRX) of transgressive black shales: Tithonian basal deposits of the Vaca Muerta Formation (Neuquén Basin, Argentina) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Recent studies have demonstrated that the mineralogical composition of shales plays an important role in unconventional hydrocarbon production (Chen et al., 2014). Mineralogy may influence the nature of the pore structure, the fracktability of these fine-grained deposits and pyrolysis reactions, all of them essential in the stimulation and extraction processes of low-permeability reservoirs (Karabakan and Yürüm, 2000; Jarvie et al., 2007; Ross and Bustin, 2009). This contribution describes and analyzes the mineralogical composition of the Tithonian basal deposits of the Vaca Muerta Formation, which resulted from two independent methodologies, QEMSCAN and DRX. The datasets comprises 19 samples distributed from the austral to the central sectors of the Neuquén Basin (Fig. 1a). The sampled sediments were deposited during the marine transgression of the early Tithonian (Fig. 1b) and accumulated under bottom conditions that favored the preservation of organic matter. The studied interval is the most important source rock of the basin. Previous geochemical studies (Spalletti et al., 2014) showed that the basal interval comprises fine-grained sediments with a very variable composition (Fig. 3), ranging from pure siliciclastic to mixed (carbonate/ siliciclastic) mudstones. Despite this compositional variability, macroscopically in the field only three main facies were recognized: greenish mudstones, yellowish mudstones and dark grey mudstones. The first two facies are commonly distributed in the marginal areas of the basin, whereas the latter is more characteristic of basinal regions (Fig. 2, Table 1). The samples were analyzed with conventional optical methods and by X-ray diffractometry (whole rock and
Keywords: Dark grey mudstones, DRX, QEMSCAN, Vaca Muerta Formation, unconventional reservoirs.